From immutable identity to plastic architecture: Topological turning points in the human brain across the lifespan - Goshu, Belay Sitotaw (Brazilian Journal of Science, 2026)
Brain network topology evolves nonlinearly across the lifespan, with turning points marking inflections in metrics like global efficiency and modularity, while connectome fingerprints capture individual stability. These features, when integrated, hold untapped potential for predicting cognitive and mental health trajectories, yet their interactive prognostic value remains underexplored amid rising neurodegenerative burdens. This study aimed to delineate individual variability in topological turning points and fingerprint stability, and then harness their synergies to forecast longitudinal outcomes, advancing precision neuroimaging for aging. In a cohort of 736 participants (ages 6–94), we identified four turning points via generalized additive models on diffusion MRI-derived networks. Fingerprint stability was quantified via intra-individual correlations (N = 150 longitudinal subsample). Predictive linear models (N = 150, 20-year follow-ups) integrated baseline fingerprints, turning point interactions, and genetic/environmental covariates to prognose cognitive/mental health declines. Turning points exhibited bimodal age distributions (e.g., global efficiency rank 1: 29.6 ± 18.7 years) with decreasing magnitudes and genetic-null correlations (r ≈ 0). Fingerprints showed high stability (0.907 ± 0.043), decaying across epochs (p = 0.002), and were heritably anchored (r = 0.809). Models achieved R² = 0.746 (cognitive) and 0.706 (mental health), driven by reserve × turning point interactions (β = -0.0055), stratifying high-risk accelerations (d = 0.115). We pioneer hybrid fingerprint-turning point frameworks, revealing epochal reconfiguration hotspots and archetype-based risk profiles, extending static Connectomics to dynamic, individualized chronometers. Topological turning points and fingerprints synergize as biographical scaffolds of brain health, demystifying heterogeneous aging. Deploy fingerprint-tailored screenings at turning point thresholds to preempt declines via targeted interventions.